Improving performance and financial viability of irrigation systems in India and China - International Water Management Institute (International Water Management Institute, 2006)
China and India face similar challenges in managing their irrigation economies. Both are developing nations with large agricultural populations, high population densities and a high proportion of agriculture under irrigation. Both are facing challenges in financing existing irrigation systems in the face of broader economic reforms. And in both countries, groundwater provides a particular challenge since it is a major source of irrigation, but with accelerating declines in both quantity and quality. Problems in financing surface irrigation systems, worries about continued groundwater table declines along with cost implications for both farmers and the energy industry, and a range of other issues have raised serious concerns over the future sustainability of irrigated systems and food security. As a result, there is now near unanimous agreement in both countries on the need to formulate practical strategies to manage the future of their irrigation economies. India and China are trying different paths when responding to their water problems and the management of public and private irrigation infrastructure. Yet, China?s experience with alternative institutional arrangements could provide useful direction to India?s equally complex surface and groundwater irrigation systems.